Application of a New Statistical Model for Measurement Error to the Evaluation of Dietary Self-report Instruments. Issue 6 (November 2015) - Freedman, Laurence S.; Midthune, Douglas; Carroll, Raymond J.; Commins, John M.; Arab, Lenore; Baer, David J.; Moler, James E.; Moshfegh, Alanna J.; Neuhouser, Marian L.; Prentice, Ross L.; Rhodes, Donna; Spiegelman, Donna; et al.
Abstract : Most statistical methods that adjust analyses for dietary measurement error treat an individual's usual intake as a fixed quantity. However, usual intake, if defined as average intake over a few months, varies over time. We describe a model that accounts for such variation and for the proximity of biomarker measurements to self-reports within the framework of a meta-analysis, and apply it to the analysis of data on energy, protein, potassium, and sodium from a set of five large validation studies of dietary self-report instruments using recovery biomarkers as reference instruments. We show that this time-varying usual intake model fits the data better than the fixed usual intake assumption. Using this model, we estimated attenuation factors and correlations with true longer-term usual intake for single and multiple 24-hour dietary recalls (24HRs) and food frequency questionnaires (FFQs) and compared them with those obtained under the "fixed" method. Compared with the fixed method, the estimates using the time-varying model showed slightly larger values of the attenuation factor and correlation coefficient for FFQs and smaller values for 24HRs. In some cases, the difference between the fixed method estimate and the new estimate for multiple 24HRs was substantial. With the new method, while four 24HRs had higher estimated correlations with truth than a single FFQ for absolute intakes of protein, potassium, and sodium, for densities the correlations were approximately equal. Accounting for the time element in dietary validation is potentially important, and points toward the need for longer-term validation studies. Abstract : Supplemental Digital Content is available in the text.